A Contribution made by Shokan Ualikhanov to the History of Middle Ages in Central Asia - Serubaeva, Aurika Temirkhanovna; Sarsambekova, Arna Saparkalievna (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
Shokan Ualikhanov is a scientist who made a huge contribution to the history of Central Asia. Shokans works were not only known worldwide while he was alive but also were of great value to science these days. He was not only noticed by virtue of his special talent, knowledge, good observance and high intelligent skills and being an orientalist hopeful about the future among the highly-qualified Russian scientists but also on top of that he was the first Kazakh scientist who left a considerable mark on European science and culture. Followed by the outstanding Marko Polo, Shokan Ualikhanovs travel to Kashgar was the first brave deed by giving a many-sided discription of blind spots in Cetral Asia and introducing them to Europe. In this research Shokan Ualikhanovs contibution to the study of the history of Middle Ages in Cetral Asia was realized, his works in this field were analized.